2012
DOI: 10.1111/j.1365-2249.2012.04633.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of apoptotic cells by macrophages in anti-neutrophil cytoplasmic antibody-associated systemic vasculitis

Abstract: Summary Anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis (AAV) is a group of autoimmune diseases, including granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA). It is not known why ANCA develop, but it has been shown that they participate in pathogenesis by activating polymorphonuclear neutrophils (PMNs). In this study we hypothesize that dysregulation of phagocytosis in AAV leads to the accumulation of apoptotic neutrophils seen in association with blood vessels in AAV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…However, there was a statistically significant increase in the overall absolute numbers of monocytes in patients with active AAV compared with patients in remission. In agreement with our results, previous studies examining patients with AAV in remission also found no change in the proportion of monocyte subsets in AAV . As intermediate monocytes express ANCA antigens and activatory Fcγ receptors, and are known to be major secretors of proinflammatory cytokines such as TNF‐α , it is a little surprising that this cell type is not relatively increased in AAV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, there was a statistically significant increase in the overall absolute numbers of monocytes in patients with active AAV compared with patients in remission. In agreement with our results, previous studies examining patients with AAV in remission also found no change in the proportion of monocyte subsets in AAV . As intermediate monocytes express ANCA antigens and activatory Fcγ receptors, and are known to be major secretors of proinflammatory cytokines such as TNF‐α , it is a little surprising that this cell type is not relatively increased in AAV.…”
Section: Discussionsupporting
confidence: 92%
“…The non‐classical population accounts for approximately 7–10% of circulating monocytes in healthy individuals, and evidence would suggest that these cells patrol the endothelium and respond to viral antigens . Studies have demonstrated a significantly increased proportion of intermediate monocytes in various inflammatory conditions, such as in patients with rheumatoid arthritis or patients at high cardiovascular disease risk , and studies have examined some data on the monocyte populations in AAV patients .…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of LDGs has been reported to be as high as 17% [42]. LDGs have never been described in AAV, and in our previous studies on monocyte subpopulations in AAV we did not detect any contaminations of neutrophils in that range [23,46]. The PBMC fraction of patients and controls in our present study was more than 99% pure according to flow cytofluorometry analysis.…”
Section: Discussionsupporting
confidence: 55%
“…We confirmed a decrease in the proportion of circulating plasmacytoid (p)DCs in human non-infectious uveitis, but were unable to ascertain a significant increase in CD1c-positive myeloid DCs (mDC1) ( 16 , 46 , 47 ). This is likely to be explained due to a different uveitis population.…”
Section: Discussionmentioning
confidence: 68%